Kaleidoscopic imaging patterns of complex structures fabricated by laser-induced deformation - Haoran Zhang (Nature Portfolio, 2016)
Complex surface micro- and nanostructures can be useful in many device applications, but are challenging in terms of controllability, low cost and high throughput. Here the authors have fabricated quasi 3D structures by the thermal deformation of simple two-dimensional laser-induced patterns.